One-step hydrothermal growth of carbon nanofibers and insitu assembly of Ag nanowire@carbon nanofiber@Ag nanoparticles ternary composites for efficient photocatalytic removal of organic pollutants. (May 2018) - Liu, Xin; Chen, Changfeng; Ye, Hongwu; Jia, Yushuai; Wu, Yiyun; Jin, Ailing; Wang, Yabin; Chen, Xiangshu
Abstract: The growth of Ag nanowire@carbon nanofiber@Ag nanoparticles (denoted as Ag NW@CNF@Ag NPs) is achieved by a one-step, template-free hydrothermal method using Ag3 PO4 -AgCl as the catalyst precursor and naturally available glucose as the carbon source. In the hydrothermal process, freshly prepared AgCl together with the active Ag 0 particles produced by the Ag3 PO4 –glucose redox reaction cocatalyzes the growth of tubular CNFs and leads to in situ assembly of the coaxial one-dimensional nanostructure of Ag NW@CNF, with ultrasmall Ag NPs well dispersed outside. The structure and composition are characterized using various advanced microscopic and spectroscopic techniques. The fabricated Ag NW@CNF@Ag NPs composite displays superb catalytic activities for the photodegradation of the organic pollutant methylene blue under visible light, which is contributed by the excellent adsorption ability of CNFs as well as the unique electron transport property afforded by the synergistic effect between Ag NW-Ag NP and conductive CNF. Coupled with economical, environmentally friendly synthetic process, sustainability of precursor, and versatility of material, the novel ternary composite developed in this study paves a new way for the fabrication of other carbon material-based hybrids to improve heterogeneous catalysis and solar-driven photocatalytic applications. Graphical abstract: Image